2014
DOI: 10.4103/2230-8229.128770
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional online survey of compulsive internet use and mental health of young adults in Malaysia

Abstract: Background:The last decade has seen the emergence of the internet as the prime communication medium changing the way people live and interact. Studies from various countries have reported on internet addiction and its association with mental health, but none have come from Malaysia.Objectives:We aimed at assessing the frequency of the use of various internet applications and exploring the association of compulsive internet use with mental health and socio-demographic factors.Materials and Methods:A cross-secti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0
1

Year Published

2015
2015
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 36 publications
3
11
0
1
Order By: Relevance
“…This study also revealed that students logging on longer online and having a computer at home are more likely to be Internet addicts. This finding is in agreement with various previous studies (Hawi, 2012;Kutty & Sreeramareddy, 2014;Sasmaz et al, 2014;Siciliano et al, 2015). Moroccan high school students could be spending longer time online as a result of the increasing speed of the Internet in Morocco and its remarkable affordability along with the widespread adoption of home computers and smartphones.…”
Section: Internet Use Patternssupporting
confidence: 93%
“…This study also revealed that students logging on longer online and having a computer at home are more likely to be Internet addicts. This finding is in agreement with various previous studies (Hawi, 2012;Kutty & Sreeramareddy, 2014;Sasmaz et al, 2014;Siciliano et al, 2015). Moroccan high school students could be spending longer time online as a result of the increasing speed of the Internet in Morocco and its remarkable affordability along with the widespread adoption of home computers and smartphones.…”
Section: Internet Use Patternssupporting
confidence: 93%
“…Moreover, watching and downloading both video and music was the most represented activity, as in the European study of Durkee et al (2012). Given the increase of these behaviors (Kutty & Sreeramareddy, 2014), they should be further studied.…”
Section: Tablementioning
confidence: 98%
“…For example, modern Malaysia marries more traditionally collectivistic cultures which emphasize conscientiousness and the desire to "save face" (Mastor, Jin, & Cooper, 2000;Santos, Varnum, & Grossmann, 2017) with increasingly widespread social media use. The latter encourages open, expressive and disclosive communication and gives voice to difference and dissent (Kutty & Sreeramareddy, 2014;Willnat & Aw, 2014). Participants' apparent curiosity regarding mental illness-despite associated stigma-seems to reflect the cultural importance placed on education and learning (Verbik & Lasanowski, 2007).…”
Section: Resultsmentioning
confidence: 99%